Análise da resposta dinâmica de um veículo sob entradas provenientes de irregularidades em estradas usando um modelo de meio carro - Valetta, Bruno Delalibera (Universidade Federal de São Carlos, 2023)
The Brazilian transport matrix is mainly composed of road transport, meaning that the country has more than 1.7 million kilometers of highways, of which 66% have problems in their state of conservation. Monitoring the quality of these roads is precarious and difficult due to their length. Therefore, several studies propose alternative forms for this monitoring, one of them being the use of accelerometer signals present in smartphones to detect irregularities on the road. Thinking about this detection method, the present study aimed to analyze the response signal of a half-car model when subjected to known inputs that represent road irregularities: bump, pothole, roadstuds and raised crossing lane. The analysis of the results allowed the identification of patterns in these signals, as well as the effect of the vehicle's speed variation on the signals, allowing the use of this knowledge in future studies that aim to identify road irregularities from accelerometer data.
Analysis of the dynamic response of a vehicle under inputs from road irregularities using a half-car model
Keywords: Detecção de irregularidades; Análise de sistemas dinâmicos; Vibrações; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS